Impact of home spirometry on medication adherence among adolescents with cystic fibrosis. Issue 4 (19th February 2018) - Shakkottai, Aarti; Kaciroti, Niko; Kasmikha, Lauren; Nasr, Samya Z.
Abstract: Objective: Medication adherence among adolescents with cystic fibrosis (CF) is often suboptimal and this has significant impact on their health and quality of life. The purpose of the study was to evaluate the impact of frequent home pulmonary function (PFT) monitoring on medication adherence among adolescents with CF. Hypothesis: We hypothesized that weekly home PFT monitoring will improve adherence while not significantly adding to the treatment burden. Methods: Individuals aged 12‐21 years with CF were provided a spirometer to measure PFTs weekly for 1 year. Results were reviewed weekly via telephone. PFT data were downloaded from the device during quarterly clinic visits. Adherence was calculated from prescription refill data and compared to the previous year. Perceptions of treatment burden were assessed using the CF questionnaire‐revised (CFQ‐R) quality of life measure. Health outcome measures including nutritional status and PFTs from clinic were collected for the study period and the year prior. Results: Thirty‐nine subjects participated in the study. Mean age was 15.89 ± 2.18 years and 54% were female. Mean adherence to weekly spirometry monitoring was 59.47 ± 24.60%. Values generated on the device showed good correlation with those obtained in clinic. Mean medication possession ratio (MPR) was 60% in the previous year and 65% during the study ( P = 0.04). Mean treatment burden scaled score on the CFQ‐R was 68 at enrollment and 66 at study completion ( P = 0.14). Conclusions: Frequent home PFT monitoring is feasible in CF adolescents and could successfully improve medication adherence without significantly impacting treatment burden.